2015
DOI: 10.4049/jimmunol.1401026
|View full text |Cite
|
Sign up to set email alerts
|

Group V Secreted Phospholipase A2 Is Upregulated by IL-4 in Human Macrophages and Mediates Phagocytosis via Hydrolysis of Ethanolamine Phospholipids

Abstract: Studies on the heterogeneity and plasticity of macrophage populations led to the identification of two major polarization states: classically activated macrophages or M1, induced by IFN-γ plus LPS, and alternatively activated macrophages, induced by IL-4. We studied the expression of multiple phospholipase A2 enzymes in human macrophages and the effect that polarization of the cells has on their levels. At least 11 phospholipase A2 genes were found at significant levels in human macrophages, as detected by qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 88 publications
2
72
0
1
Order By: Relevance
“…Prior studies have also demonstrated that sPLA 2 -V is necessary for the development of allergic inflammation in the HDM (68) and OVA/alum (69) models of allergic airways disease, and that while sPLA 2 -V is involved in maturation and antigen processing in DCs (68), macrophages expressing sPLA 2 -V are sufficient to transfer antigen sensitization mice (20). Studies in human macrophages support a role for sPLA 2 -V in phagocytosis and antigen processing (70). Given our findings of a marked alteration in the adaptive immune response to inhaled allergen, it will be important in future studies to clarify the respective roles of these sPLA 2 s in macrophage function.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have also demonstrated that sPLA 2 -V is necessary for the development of allergic inflammation in the HDM (68) and OVA/alum (69) models of allergic airways disease, and that while sPLA 2 -V is involved in maturation and antigen processing in DCs (68), macrophages expressing sPLA 2 -V are sufficient to transfer antigen sensitization mice (20). Studies in human macrophages support a role for sPLA 2 -V in phagocytosis and antigen processing (70). Given our findings of a marked alteration in the adaptive immune response to inhaled allergen, it will be important in future studies to clarify the respective roles of these sPLA 2 s in macrophage function.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, several functions of sPLA 2 s in mice, as depicted in Fig. 2 , appear to be conserved in humans ( 55,70,74,93,117,134 ). Further advances in this research fi eld and their integration for therapeutic applications are expected to benefi t from improved lipidomics that will allow monitoring of individual sPLA 2 s and associated lipid metabolisms within specifi c tissue niches.…”
Section: Discussionmentioning
confidence: 99%
“…This transgenic phenotype is attributable to aberrant hydrolysis of surfactant phospholipids (dipalmitoyl-PC) and is apparently eicosanoid-independent. Although sPLA 2 -V was previously thought to be upregulated by pro-infl ammatory stimuli (as in the case of sPLA 2 -IIA) ( 90,91 ), it has recently become obvious that its expression is induced by the Th2 cytokines, IL-4 and IL-13, much more potently than by pro-infl ammatory stimuli including LPS, zymosan, and Th1 cytokines ( 74,92,93 ). Indeed, sPLA 2 -V is expressed in IL-4-driven M2 macrophages and Th2 cells, which facilitate Th2-type immunity while attenuating Th1-or Th17-type immunity.…”
Section: S Participate In Diverse Biologicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulation of 16:1n-9 was also examined in monocytes differentiated toward macrophages with recombinant macrophage colony-stimulating factor (Rubio et al, 2015). While the level 16:1n-9 greatly increased along the differentiation process, 16:1n-7 content did so to a much lesser extent ( Figure S1).…”
Section: Stimulation Of Monocytes By Aa Induces the Accumulation Of Amentioning
confidence: 98%